MENGEMBANGKAN KECERDASAN EMOSI DAN SPIRITUAL - Rachman, Arief (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2005)
Human Intelligent is note only verbal, but it has variety of brand. At least, there are five kinds of intelligences of human being: spiritual, emotional, rational, social and physical. The fifty kinds of intelligences have to get the same opportunity to expand, especially emotional and spiritual intelligence, because those two potencies of intelligences are often disregarded.To develop all potencies of intelligence above requires five-education phase: (a) the recognition, (b) the experience, (c) the innovation, (d) the comprehension, and (e) the practice. In addition, it needs good cooperation between teacher and parent. Each has to give guidance, which has orientation, democratic and full of affection.Keyword: potencies of intelligence and intelligent education.